Reuse of water and sludge in agriculture: new technologies for the treatment (Research, Society and Development, 2023)
The treatment and reuse of water in Brazil is one of the most discussed issues in the agricultural field. In recent years, the scarcity of water changes in the rainfall regime has impacted production. The management of water resources aims to make better use of one of the means that most uses water, agriculture. Reuse and treatment are essential through innovative technologies that corroborate better water efficiency to extract the maximum water capacity and avoid waste. In an increasingly sustainable scenario, which seeks cleaner environments, with little or no emission of pollutants and losses of water resources, the reuse and treatment or possible disposal in a correct way is always an object of study to achieve the effect in use. of water, seeking better production in crops and reducing environmental impacts. This work aims to analyze the historical evolution of technologies used to treat wastewater and sewage sludge. We can see that the theme has grown in recent years, and several technologies are emerging to improve water treatment more efficiently and effectively. Thus, we conclude that the reuse of wastewater and sewage sludge has a large field of study and application in agriculture.